Effect of pulsed electron beam treatment on the physico-mechanical properties of hydroxyapatite-coated titanium; Ceramics International; Vol. 42, iss. 1, pt. B - Surmeneva M. A. Maria Alexandrovna; Chudinova E. A. Ekaterina Aleksandrovna; Grubova I. Yu. Irina Yurievna; Korneva O. S. Olga Sergeevna; Shulepov I. A. Ivan Anisimovich; Teresov A. D. Anton Dmitrievich; Koval N. N. Nikolay Nikolaevich; Mayer J.; Oehr C.; Surmenev R. A. Roman Anatolievich (2016, 2016)
Title screen